2003
DOI: 10.1016/s0924-7963(03)00029-0
|View full text |Cite
|
Sign up to set email alerts
|

Particle fluxes in the ocean: comparison of sediment trap data with results from inverse modeling

Abstract: Biological production lowers the CO 2 concentrations in the surface layer of the ocean, and sinking detritus ''pumps'' nutrients and CO 2 into the deep ocean. Quantifying the efficiency of the biological pump is a prerequisite for global CO 2 budgets. Sediment traps are commonly used to directly measure the vertical particle flux; however, for logistical and financial reasons, traps cannot provide area-wide data sets. Moreover, it has been shown that sediment traps can under-or overestimate particle fluxes con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
38
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(46 citation statements)
references
References 51 publications
8
38
0
Order By: Relevance
“…An evaluation of trapping efficiency of sediment traps (Yu et al, 2001) suggests a low and erratic efficiency in the mesopelagic. This is also confirmed by a comparison between sediment trap data and inverse modeling results (Usbeck et al, 2003). The low trapping efficiency of sediment traps at mid-depth might explain the systematic off-set between modeled fluxes and trap results.…”
Section: Ocean Productivity and Exportsupporting
confidence: 69%
“…An evaluation of trapping efficiency of sediment traps (Yu et al, 2001) suggests a low and erratic efficiency in the mesopelagic. This is also confirmed by a comparison between sediment trap data and inverse modeling results (Usbeck et al, 2003). The low trapping efficiency of sediment traps at mid-depth might explain the systematic off-set between modeled fluxes and trap results.…”
Section: Ocean Productivity and Exportsupporting
confidence: 69%
“…Global models might be able to provide additional constraints on the power law exponent by optimizing the exponent so as to best reproduce global dissolved inorganic carbon, phosphate or alkalinity fields (e.g. Usbeck et al, 2003). Ultimately a better understanding of the processes that affect POC fluxes in the water column should produce a mechanistically based model to replace the empirical power law parameterization (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Another experiment was conducted to enforce the trap data in the model over larger horizontal distances by applying smoothness constraints. This run showed that the smaller trap fluxes in the upper water column were inconsistent with the measured distributions of oxygen, nutrients and carbon in the ocean, because enforcing these fluxes over great areas led to un- realistic simulations for oxygen, nutrients and carbon (Usbeck et al 2003). …”
Section: Comparison With Sediment Trap Datamentioning
confidence: 94%